Database Management Systems (2000–2026): A Scopus-Based Bibliometric Review of Research Streams and Key Contributor - Judijanto, Loso (West Science Information System and Technology, 2026)
The current research intends to analyze the knowledge structure and research trends of the DBMS by using a bibliometric approach to study articles published in the Scopus database between 2000 and 2026. This will be achieved using the VOSviewer as the main software for analyzing authors' networks, citations and keywords' co-occurrences. As expected, the findings reveal that research within the DBMS area has become increasingly interdisciplinary with notable influences from fields such as health care and bioinformatics and data science. In terms of authorship patterns, it is evident that collaboration within DBMS research happens in clusters. This is an indication of the presence of well-coordinated intra-cluster collaboration and a lack of inter-cluster collaboration. The findings from the citation analysis show that there are key publications within DBMS research that have been highly cited due to their contribution to developing the discipline. Finally, from the keyword co-occurrences, it is clear that the trend within DBMS research has shifted from more traditional subjects to newer areas such as artificial intelligence and machine learning. The findings highlight the growing complexity and integration of DBMS within modern digital ecosystems, while also emphasizing the need for enhanced global collaboration and innovation-driven research. This study provides valuable insights for researchers and practitioners in understanding the trajectory and future directions of DBMS research.